MARKETING OF HIGH-TECHNOLOGY PRODUCT: STRATEGI PEMASARAN & PENGEMBANGAN PRODUK BERBASIS TEKNOLOGI MP3 - Silvia Margaretha (Journal of Management and Business, 2006)
In today's highly competitive environment, high technology-based companies must know rapid technological changes in marketing fields. Rapid technological changes force the companies to develop their products. There are several approaches to develop their products including technology push, platform product, process-intensive and customized products. Based upon such approaches, they can anticipate the short product life cycle. The companies must have a proactive market driving strategy to cope with market uncertainty, technological uncertainty and competitive volatility that characterize high-tech industries. With the market driving strategy, the companies can have capabilities to lead the dynamics through value creation, change and leadership.